Mainillnesses that affect the sheep production in the tropic - Benavides Ortíz, Efraín (Spei Domus, 2023)
The use of the smallest species as the ovine and caprine is a production alternative in Colombia. These species stand out because of the adaptative capacity to adverse environments, and due to their high reproductive rate, proven in multiple births, which entails to obtain good meat production. Furthermore, this species are recognized because of presenting resistance to certain illnesses that are usually lethal in other species and because the production systems still follows the traditional handling. However, there is a wide listing of etiologies of infectious nature that can produce important illnesses in the ovine-caprine industry. These include viral, bacterial, fungic and parasitic agents; some of them are of obligatory notification and it implies to recognize their importance at zoonotic level.